Cajanus Cajan Leaf and Ginger Increase Antioxidant Defence in Pancreatic Diabetic Rats: An Immunohistochemical Study - Wresdiyati, Tutik; Cahyani, Bella Dinar Fauqii; Alfarisi, Hamzah; Sa'diah, Siti; Astawan, Made (Jurnal Veteriner; Vol 25 No 1 (2024)DO - 10.19087/jveteriner.2024.25.1.1, 2024)
Hyperglycemia in diabetes mellitus results in stress oxidative condition. This study aims to analyze the antioxidant defence in pancreatic experimental-diabetic rats treated with a combined extract of Cajanus cajan leaf and ginger, using an immunohistochemical technique for copper, zinc – superoxide dismutase (Cu,Zn-SOD). A total of 25 male Sprague Dawley rats were used in this study.  The rats were randomly divided into five groups; normal control group (NC), diabetic group (DM), two groups DM treated with a different dose combination of Cajanus cajan leaf extract and ginger extract (DME and DMF), and DM treated with glibenclamide (DMG). This study used 110 mg/kg BW alloxan induction to obtain diabetic conditions, and the treatments of the extract were conducted for 28 days.  The pancreatic tissues were processed using the paraffin standard method and an immunohistochemical technique using monoclonal antibody Cu,Zn-SOD. The results showed that a combination of Cajanus cajan leaf extract and ginger extract lowered the level of blood glucose, increased body weight, and increased the level of Cu,Zn-SOD content in pancreatic tissues of experimental-diabetic rats. This study concluded that combining Cajanus cajan leaf extract and ginger extract increased antioxidant defence in pancreatic organs of experimental-diabetic rats.